2013
DOI: 10.1118/1.4795757
|View full text |Cite
|
Sign up to set email alerts
|

ROC analysis in patient specific quality assurance

Abstract: The optimal threshold values that were determined represent a maximized test sensitivity and specificity and are not subject to any user bias. When applied to the datasets that we studied, our results suggest the use of patient specific QA as a safety tool that can effectively prevent large errors (e.g., σ > 3 mm) as opposed to a tool to improve the quality of IMRT delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 37 publications
1
65
0
1
Order By: Relevance
“…Assessment of the performance of different patient‐specific treatment QA acceptance criteria was done by applying receiver operating characteristic (ROC) analysis. While this methodology originally had been used to quantify the value of a diagnostic imaging test, it was also successfully applied to reveal the error detection capabilities and limits for IMRT QA . For both IQM and ArcCHECK QA, the measures of sensitivity (true positive rate) and specificity (true negative rate) were computed for different QA tests at varying decision thresholds.…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of the performance of different patient‐specific treatment QA acceptance criteria was done by applying receiver operating characteristic (ROC) analysis. While this methodology originally had been used to quantify the value of a diagnostic imaging test, it was also successfully applied to reveal the error detection capabilities and limits for IMRT QA . For both IQM and ArcCHECK QA, the measures of sensitivity (true positive rate) and specificity (true negative rate) were computed for different QA tests at varying decision thresholds.…”
Section: Methodsmentioning
confidence: 99%
“…Carlone et al . investigated the use of receiver operating characteristic (ROC) methods in order to set tolerance limits for γ evaluations.…”
Section: Review Of Reported Imrt Measured Vs Calculated Agreementmentioning
confidence: 99%
“…(5) Many studies have tried to find the best cutoff to separate acceptable and unacceptable beams. Carlone et al (6) provided optimal threshold values with introducing random multileaf collimator (MLC) position errors, which can maximize the sensitivity and specificity of the test by ROC analysis. McKenzie et al (7) showed that different IMRT QA devices and QA evaluation methods should have different cutoffs after comparing the result of different IMRT QA devices and QA evaluation methods to a “true” IMRT QA result.…”
Section: Introductionmentioning
confidence: 99%